2018
DOI: 10.1016/j.asjsur.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Is the superior laryngeal nerve really safe when using harmonic focus in total thyroidectomy? A prospective randomized study

Abstract: To the best of our knowledge, this is the first study comparing conventional technique with HF in total thyroidectomy, focusing on the function of the external branch of the superior laryngeal nerve using laryngostroboscopy; results showed that HF is as safe as the conventional technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…In the studies comparing vascular closure systems and conventional suture technique in the literature, complications such as postoperative hemorrhage, recurrence laryngeal nerve injury and hypoparathyroidism were evaluated in the morbidity parameters (3,4,6,7), and data on EBSLN injury were insufficient. The only study in this regard is a prospective randomized study by Arslan et al (12) that compares the harmonic scalpel with conventional suture ligation technique in thyroidectomy. Unilateral activity loss 1 (7) 0 (0) 1 (7) 0 (0) 0 (0) 0 (0) Unilateral neurogenic involvement 0 (0) 0 (0) 1 (7) 1 (7) 0 (0) 0 (0)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the studies comparing vascular closure systems and conventional suture technique in the literature, complications such as postoperative hemorrhage, recurrence laryngeal nerve injury and hypoparathyroidism were evaluated in the morbidity parameters (3,4,6,7), and data on EBSLN injury were insufficient. The only study in this regard is a prospective randomized study by Arslan et al (12) that compares the harmonic scalpel with conventional suture ligation technique in thyroidectomy. Unilateral activity loss 1 (7) 0 (0) 1 (7) 0 (0) 0 (0) 0 (0) Unilateral neurogenic involvement 0 (0) 0 (0) 1 (7) 1 (7) 0 (0) 0 (0)…”
Section: Discussionmentioning
confidence: 99%
“…Among these techniques, the more invasive and time-consuming cricothyroid muscle EMG is the most accurate diagnostic method (9,20). The risk of iatrogenic partial or complete EBSLN injury varies between 0% and 6% after thyroidectomy and this rate increases up to 60% when EMG is performed (12,14,18,21).…”
Section: Table 1 the Distribution Of Demographic Characteristics Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies related to EBSLN have used patient self‐reports on voice changes, subjective acoustic analysis of the investigator the GRABS scale, patient‐reported questionnaires (Voice Handicap Index‐10 and SLN Impairment Index‐5), objective acoustic analysis (multidimensional voice profile, and voice range profiles), and laryngoscopic or stroboscopic evaluation of vocal folds . Although these postoperative non‐EMG methods might not yield constant, standardized and reliable findings, some researches used them as the reference methods for EBSLN integrity in the studies related to the identification methods for EBSLN . However, we had a question concerning whether CT muscle twitch inspection, well‐known as a good identification and verification method for EBSLN integrity, could be an alternative to CT muscle EMG in the fields of EBSLN or PTD research.…”
Section: Discussionmentioning
confidence: 99%
“…et al (45) reported that the use of the harmonic scalpel was safe and did not increase de rates of EBSLN injury when postoperative laryngostroboscopy was analyzed. The authors emphasize that the device should not be applied within less than 2 mm from neural structures and should not be continuously activated for longer than 15 seconds.…”
Section: Potenza Et Al Injury Of the Ebsln In Thyroid Surgerymentioning
confidence: 99%